Protagonismo feminino e violência em Simá - romance histórico do Alto Amazonas -, de Lourenço Araújo e Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The dissertation Female Protagonism and Violence in Simá - Historical Romance of Alto Amazonas -, by Lourenço Araújo e Amazonas, deals with violation, virginity and female protagonism in Romanticism, considering a critical analysis of Simá. With the aim of addressing the proposed theme, the text is organized as follows: the first section presents the origins of the romance genre and the definitions of romanticism for understanding the female protagonism exercised by Simá, the character who titled the work; then, a second section highlights the ethnocentric look and the process of acculturation of the indigenous people that is justified by the supposed inferiority of the indigenous peoples, answering the questions of misogyny and violence linked to the behavior of the male characters and the position of the colonizers; later, in the third section, the text addresses gender issues and the female condition that permeates the romantic writing of Lourenço Araújo e Amazonas. Thus, from the critical reading of Simá - Historical Romance of Alto Amazonas -, by Lourenço Araújo e Amazonas, they are approached as themes pertaining to virginity, rape and female protagonism, themes for which we resort to the contributions of Howard Bloch, Pierre Bourdieu and Mary Del Priore, among others, which support the critical analysis of the condition of women over time. Therefore, the work relies on the theoretical perspectives of Joseph Campbell, Mikhail Bakhtin and György Lukács, whose readings were fundamental to think about Romanticism and the triggering of the narrative, the behavior of the characters within the work and how the social context directly interferes in this construction. The analyses were carried out by the method of Theory of Literary and Cultural Residuality, by Roberto Pontes, hereinafter TRLC, which offers the subsidies to explain the relations of the literary text with the past, with other times and spaces and of which we highlight as guidelines related to the theory of the Social Imaginary.
Keywords: Romantismo; Misoginia na literatura; Miscigenação na literatura; Mulheres e literatura; Protagonismo feminino; LINGUÍSTICA, LETRAS E ARTES: LETRAS; Romantismo; Relações de Poder; Misoginia; Miscigenação; Residualidade